Ofélia: percurso íntimo de uma imagem idealizada - Rampini, Lúcia Castanho Barros (2013)
The main core of this thesis is the series of photographs that have reference to the fictional character, Ophelia, originally presented and described by Shakespeare in Hamlet (1603), and later painted by John Everett Millais ("Ophelia", 1851-2). It is an interdisciplinary study, which falls within the area of visual arts and culture. The initial research lays on the relationship between women and death, in the nineteenth century, the survival of the image of Ophelia till the twenty-first century and the indulgences that are imposed on women by patriarchal society. The thesis is divided into six core parts that connect to each other, alternating women's history, representation and artistic creation. To make these connections, we worked on texts that elucidate questions related to female suicide, melancholy, and also the image and its survival time. We also refer to Elizabeth Siddal, the young woman who posed for the Millais painting, and the intricacies between fiction and reality. This study allowed us to make a deep reflection on the condition of women and female artists in a society that has Ophelia as a contemporary metaphor for the modern romantic who struggles with conflicting feelings of mutual misunderstanding, unrequited love, and desperate desire, seeking final release in death. The trajectory of the development of this work led to the creation of series of photographs, drawings and paintings, of which a selected part is here presented.